2015
DOI: 10.1371/journal.pone.0117141
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Locally Advanced Rectal Cancer with Low Risk of Local Recurrence

Abstract: BackgroundThe routine application of neoadjuvant chemoradiotherapy for T3N0 rectal cancer remains controversial. The aim of this study was to use clinical, Magnetic resonance imaging, and pathological parameters to identify a subgroup of patients with low risk of local recurrence who might be precluded from neoadjuvant chemoradiotherapy.MethodsWe retrospectively reviewed a prospectively maintained database of consecutive rectal cancer patients who underwent curative resection. 166 pathologic confirmed T3N0 rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…According to data compiled by the European Society for Medical Oncology (ESMO) Guidelines Committee, preoperative RT or NCRT reduces LR without improving OS in middle/lower stage II/III rectal cancers . Considering the heterogeneity among literature reviews, the ESMO panelists did not recommend NCRT for upper rectal cancers (>12 cm from the anal verge) above the peritoneal reflection . Popek et al explored the role of neoadjuvant therapy for upper LARC (≥10‐15 cm), and they suggested that patients with T3 N0 tumors would not likely benefit from neoadjuvant RT and that treatment of patients with T4 N0 should be individualized .…”
Section: Relationship Between Tumor Location and Efficacy/safety Of Ncrtmentioning
confidence: 99%
See 4 more Smart Citations
“…According to data compiled by the European Society for Medical Oncology (ESMO) Guidelines Committee, preoperative RT or NCRT reduces LR without improving OS in middle/lower stage II/III rectal cancers . Considering the heterogeneity among literature reviews, the ESMO panelists did not recommend NCRT for upper rectal cancers (>12 cm from the anal verge) above the peritoneal reflection . Popek et al explored the role of neoadjuvant therapy for upper LARC (≥10‐15 cm), and they suggested that patients with T3 N0 tumors would not likely benefit from neoadjuvant RT and that treatment of patients with T4 N0 should be individualized .…”
Section: Relationship Between Tumor Location and Efficacy/safety Of Ncrtmentioning
confidence: 99%
“…A subgroup of patients with upper rectal cancer who may require a more aggressive therapy than only primary resection followed by adjuvant therapy can be identified . For patients with upper and middle T3 N0 rectal cancer with a preoperative CRM of >1 mm, the LR rate after TME is low and surgery alone may be sufficient for this group of patients . A previous study analyzed LR and survival rates of 4153 patients registered from 1995 to 1997 in the Swedish Rectal Cancer Registry .…”
Section: Relationship Between Tumor Location and Efficacy/safety Of Ncrtmentioning
confidence: 99%
See 3 more Smart Citations